EFFECTOFEXERCISESUSING DIFFERENTRESISTORSINTHE DEVELOPMENTOFTHESPECIAL STRENGTHOFTHEARMSANDTHE COMPLETIONOFJAVELINFORTHE ATHLETESOFTHESCHOOL SPECIALIZED ATHLETICS - Mohsen, Zainab Qahtan Abdul; Yaas, Saja Shuker (International Journal of Psychosocial Rehabilitation, 2020)
Athletics are different from other games as a competition between individuals to show their competence and physical ability to achieve new record numbers in the various activities and various between the boards, jumping and throwing and each type of these activities in particular performance so found the researcher to find the method of training resistors in the development of special power and achievement In the effectiveness of javelin, where the researchers chose the sample of the athletes from the specialized school of athletics to effectively throw the spear at the ages of 15-17 years and carried out the tests of the research, which includes the strength of the speed of the arms and explosive power and The various resistance exercises contributed to the development of these tests, and the researchers recommend comparisons between different training methods and training resistors.